Early lingual nerve suture under local anesthesia after wisdom tooth extraction: a case report - Godard Aurélien; Millot Gaël (EDP Sciences, 2023)
Introduction: Lingual nerve injury is one of the operative risks of mandibular wisdom tooth avulsion surgery. The anatomical relationship of the nerve to the medial side of the socket of the mandibular third molar must be known when performing the procedure. When a lesion occurs, the diagnosis may be delayed by the effect of anesthesia. In the case of a complete section, repair can be considered by direct suture of the nerve margins. It is recommended to perform this suture as soon as possible. In most cases, the lingual nerve suture is performed remotely and under general anesthesia. Observation: The case presented here describes the early repair of a lingual nerve transection after avulsion of a mandibular third molar. The procedure has been performed under local anesthesia one day after surgery and consisted of a direct suture using the previous surgical approach. Conclusion: This allows for a simplified treatment of this complication, thus shortening the management time.